2008
DOI: 10.1083/jcb.200807006
|View full text |Cite
|
Sign up to set email alerts
|

CaM kinase II initiates meiotic spindle depolymerization independently of APC/C activation

Abstract: Altered spindle microtubule dynamics at anaphase onset are the basis for chromosome segregation. In Xenopus laevis egg extracts, increasing free calcium levels and subsequently rising calcium-calmodulin–dependent kinase II (CaMKII) activity promote a release from meiosis II arrest and reentry into anaphase. CaMKII induces the activation of the anaphase-promoting complex/cyclosome (APC/C), which destines securin and cyclin B for degradation to allow chromosome separation and mitotic exit. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…In sea urchin oocytes for example, phosphoinositide-dependent Ca 2ϩ signals control progression through the cell cycle checkpoints at G 1 /S, G 2 /M, and mitosis exit (11, 29, 52, 144). The Ca 2ϩ -dependent regulation of the early division cycles has also been thoroughly studied in frog embryos, where the overall pattern is similar to that observed in sea urchin, although the opacity of Xenopus oocytes makes studying [Ca 2ϩ ] i with optical methods more difficult (56,92,101,124). Similar calcium transients also occur in mouse oocytes, in which however their precise functional role is still debated (7,43,62,72,82).…”
Section: Downstream Actions Of Ca 2ϩmentioning
confidence: 84%
“…In sea urchin oocytes for example, phosphoinositide-dependent Ca 2ϩ signals control progression through the cell cycle checkpoints at G 1 /S, G 2 /M, and mitosis exit (11, 29, 52, 144). The Ca 2ϩ -dependent regulation of the early division cycles has also been thoroughly studied in frog embryos, where the overall pattern is similar to that observed in sea urchin, although the opacity of Xenopus oocytes makes studying [Ca 2ϩ ] i with optical methods more difficult (56,92,101,124). Similar calcium transients also occur in mouse oocytes, in which however their precise functional role is still debated (7,43,62,72,82).…”
Section: Downstream Actions Of Ca 2ϩmentioning
confidence: 84%
“…66,109 Recent work has demonstrated that CaMKII regulates microtubule catastrophe during anaphase, as overexpression of a constitutively active CaMKII mutant promotes microtubule destabilization. 110 Furthermore, downregulation of CaMKIIγ in a variety of cell lines by siRNA resulted in an accumulation of prometaphase/metaphase cells, as well as cells with multipolar spindles, 67 which indicates that CaMKII is required for normal bipolar spindle formation during mitosis.…”
Section: Camk Regulation Of the Cell Cyclementioning
confidence: 99%
“…Recently, it has been shown that ciliary resorption is triggered by the addition of a specific combination of growth factors, including PDGF-AA Ca 2+ /CaM-dependent protein kinase II (CaMKII). 47 CaMKII has been shown to depolymerize meiotic spindles in Xenopus egg extracts 48 and localizes at the mammalian olfactory cilia, 49,50 suggesting that the increase in Ca 2+ and subsequent activation of CaMKII at the primary cilia may participate in the dissasembly process. It is important to note that a reduction in intracellular Ca 2+ concentration resulted in abnormally long cilia in epithelial and mesenchymal cells, 51 supporting the notion that Ca 2+ directly or indirectly can regulate ciliary retraction.…”
Section: Growth Factor-induced Ciliary Resorptionmentioning
confidence: 99%